1993
DOI: 10.1111/j.1365-2249.1993.tb05936.x
|View full text |Cite
|
Sign up to set email alerts
|

Human recombinant IL-1 receptor antagonist (IL-IRa) inhibits leukotriene B4 generation from human monocyte suspensions stimulated by lipopolysaccharide (LPS)

Abstract: SUMMARYThe efiect of human recombinant IL-1 receptor antagonist (hrlL-lRa) on leukotriene B4 (LTB4) release was investigated in activated human monocyte cultures. To stimulate LTB4 generation, LPS was used as an agonist. Detection was performed with the highly sensitive radioimmunoassay method. The cells were treated with scalar concentrations using LPS at I -IOOO ng/ml for different periods or lime. The greater LTB4 stimulaiion was found at LPS 100 ng/ml for 18 h incubation time. Preincubation of monocytes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In the current study, we revealed that LTB4-BLT1 signaling is another important mediator for DC cluster formation. It has been reported that IL-1 induces LTB4 production from neutrophils ( Smith et al, 1987 ) and that IL-1 receptor antagonist down-regulates LTB4 production from monocytes ( Conti et al, 1992 , 1993 ). Therefore, IL-1 observed in skin inflammation ( Natsuaki et al, 2014 ) may induce LTB4 production in the skin, which may lead to increased DC motility and subsequent DC cluster formation in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we revealed that LTB4-BLT1 signaling is another important mediator for DC cluster formation. It has been reported that IL-1 induces LTB4 production from neutrophils ( Smith et al, 1987 ) and that IL-1 receptor antagonist down-regulates LTB4 production from monocytes ( Conti et al, 1992 , 1993 ). Therefore, IL-1 observed in skin inflammation ( Natsuaki et al, 2014 ) may induce LTB4 production in the skin, which may lead to increased DC motility and subsequent DC cluster formation in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we stimulated macrophages with LTB 4 at a concentration of 100 nM. It has been reported that LTB 4 in excess of 100 nM is produced in human neutrophils by stimulation with granulocyte macrophage colony-stimulating factor (GM-CSF) and formyl-methionylleucyl-phenylalanine (44) and that LTB 4 levels reach 50 nM following stimulation of human monocytes with the calcium ionophore A23187 (45) or LPS (46). Thus, it is possible that macrophages are exposed to LTB 4 above the level in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous in vitro studies indicate that a wide range of phenolic compounds might exert anti-inflammatory effects by targeting the 5-LOX pathway ( Table S1 ). Thus, caffeic acid, hydroxytyrosol, resveratrol, curcumin, NDGA and quercetin are compounds with the capacity to reduce the formation of 5-HETE, LTB 4 (and its ω-oxidized metabolites), and Cys-LTs [ 107 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. Although desirable, these effects should be considered with caution since inhibition of the 5-LOX pathway could result in higher (pro-inflammatory) COX-2 metabolite levels by shunting the substrate, AA.…”
Section: Resultsmentioning
confidence: 99%